We investigated the effect of sector (position in canopy) on translocation and distribution of 13C-photosynthates in mangosteen trees and related the findings to previous analyses of fruit quality. Our experiment was conducted on three 25-year-old mangosteen trees. Tree canopies were divided into 9 sectors based on height (bottom, middle, top) and width (inner, center, outer). One branch from each sector was labeled with 13CO2 in December 2003. Immediately after labeling, 13C concentration in l - Setiawan, Eko; Poerwanto, Roedhy; Fukuda, Fumio; Sugiyama, Nobuo; Saitoh, Kuniyuki; Kubota, Naohiro (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2012)
We investigated the effect of sector (position in canopy) on translocation and distribution of 13C-photosynthates in mangosteen trees and related the findings to previous analyses of fruit quality. Our experiment was conducted on three 25-year-old mangosteen trees. Tree canopies were divided into 9 sectors based on height (bottom, middle, top) and width (inner, center, outer). One branch from each sector was labeled with 13CO2 in December 2003. Immediately after labeling, 13C concentration in leaves from middle sectors was higher than that in leaves from other positions. 13C concentration in all leaves decreased rapidly for 24 h after 13C feeding, followed by a gradual decrease. In contrast, 13C concentration increased over time in the pericarp and aril of fruits. Translocation of 13C-photosynthates into fruit was high in Sectors 4 and 5, and in top positions (Sectors 7 to 9). At 96 h after 13C feeding, the highest distribution ratio of 13C-photosynthates was observed in stems, followed in descending order by pericarp, leaf, and aril. 13C distribution ratio in the aril was generally highest in fruits from inner and center positions. The relationship between partitioning of photosynthates and quality of mangosteen fruit, which differs among sectors, has been discussed. Keywords: fruiting positions, Garcinia mangostanaL., photosynthate partitioning, 13C, tree branches